The effects of corporate reputation on the competiveness of Malaysian telecommunication service providers - Awang, Zainudin; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
The competition for customers among telecommunication firms in Malaysia is fierce. The competition among them is not only limited to new customers but also to the respective customer base. In this fiercely competitive environment, existing customers are frequently exposed to offers and counter offers from the competing firms. At the same time various persuasive messages being made to encourage customers to switch their service provider. Perhaps the corporate reputation of a firm could provide certain competitive edge which could ensure the growth and survival of a firm into the future amid the highly competitive environment. This study attempts to assess the influence of corporate reputation of the firms on their competitive advantage in the market from the customers’ perspective. The study sampled 600 individual customers who have been using the mobile service at a minimum of three years. The selected respondents have been experiencing the service provided by more than one telecommunication operators. The data were collected using self-administered questionnaires and analyzed using Structural Equation Modeling (SEM) in AMOS 6.0. The study found that the direct impact of firms’ corporate reputation on their competitive advantage in the market is not significant at ? = 0.05. Instead, the corporate reputation has an indirect impact on competitive advantage through perceived value and perceived quality of the service. In other words, the firms should communicate their favorable corporate reputation effectively to the market so that the customers’ perception level towards their products and service would arise. In other words, the firm’s corporate reputation could only help the marketability of its products or services if it could trigger the positive perception of quality and value of products or services in the mind of their potential customers. The findings provide important implications to the telecommunication operators in their effort to increase their customer base and, more importantly, to ensure the interest the customers towards the firm is preserved.